Graphene doped TiO2/p-silicon heterojunction photodiode - Hendi, A. A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2016)
The photoresponse properties of Al/p-Si/GO:TiO2/Au diodes were investigated using transient photocurrent and conductance spectroscopy techniques. The average barrier height and ideality factor values of the diodes were found to be 0.601 +/- 0.001 eV and 17.9.3 +/- 9. It is seen that the electronic parameters of the diodes depend on GO content. The obtained ideality factor is higher than unity due to the low carrier mobility of the organic interlayer. The change in the capacitance of the diodes indicates a continuous distribution of interface states. The photoresponse properties of the diodes are changed with GO content. Al/p-Si/GO:TiO2/Au having 3% GO weight exhibited the highest photosensitivity. The obtained results indicates that the prepared photodiodes can be used as a photosensor in optoelectronic device applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Graphene oxide; Titanium dioxide; Photodiode